A multilateral legal assistance protocol: Preventing fragmentation and re-territorialisation of the internet - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2013)
Ineffectual legal-assistance cooperation increasingly prompts governments to apply laws extraterritorially or to force data localisation, with dire consequences for the free flow of data and the global economy. As a result, different layers of national laws counteract and sometimes contradict one another. In response, governments conclude bilateral and multilateral treaties to resolve the problem of online crime and law enforcement. In judiciary co-operation, there are so-called mutual legal assistance treaties (MLATs) that provide for cross-border legal enforcement. Some international treaties, most notably the Council of Europe's Convention on Cybercrime, go beyond MLATs and seek to harmonise criminal laws of the signatories. Finally, bilateral and multilateral free trade agreements (FTAs) ensures that these legal measures are not disproportionate and trade barriers on legitimate commercial activities. The paper argues for the necessity to build a framework with stricter standards for legal assistance and stronger safeguards to protect civil liberties, human rights, rule of law and core principles of transparency. In turn, improved co-operation and safeguards make unilateral measures (such as data localisation requirement) superfluous - thus, the protocol would also incorporate negative rules that are often found in FTAs, to prevent governments from enacting such measures that re-territorise the internet.
Keywords: 330; IT-Recht; Rechtsdurchsetzung; Handelspräferenzen